Lack of Credit in Albania; Who is to “Blame” Analyzing the Demand - Musta, Eugen; Meka, Elvin (European Journal of Economics and Business Studies, 2015)
The last global crisis had it influence on Albanian economy as well. As the economy is still struggling to recover from the slowdown, a special attention is dedicated to lending which will in turn help investments pick up. Banks in Albania are currently flooding in excess deposits, but meanwhile the lending has hit its lowest score. What is refraining banks from lending? Is it really them to blame or maybe the demand is also part of the problem? Are businesses suffering from lack of funds to finance their activity or are they hesitating to invest and are waiting for better times to come along? The purpose of this study is to look into these questions and find the reasons behind them. This paper is focused on the demand side, analyzing some of the most important indicators influencing the demand for credit like enterprises growth, profits, planned investments, working capital needs, liquidity, etc. In order to get better understanding on the behavior of these variables the enterprises are divided in four groups by size criteria. The analysis is covering data for five-year timeframe, which is corresponding with the start of the economic slowdown. To help getting a prospect of the present and the future perceptions of the economic situation, a survey was conducted on a small sample of enterprises. This study comes to the conclusion that the demand for credit is growing, but what’s keeping businesses from applying for it, is mainly because of high interest rates and cost of credit, the study ends with some recommendations toward the solution.
Keywords: Albania, demand for credit, credit gap, banking system, economic slowdown